Blockchain-based hierarchical and multi-level smart service transaction supervision framework for crowdsourcing logistics - Chuntang YU; Zhigeng HAN; Zhiyuan LI; Liangmin WANG (网络与信息安全学报)
In view of the security threats such as forgery,deception,privacy disclosure and non-traceability caused by the lack of transaction supervision for crowdsourcing logistics in the modern service industry,a blockchain-based hierarchical and multi-level smart service transaction supervision framework for crowdsourcing logistics was proposed.Firstly,the framework adopted the two-stage supervision system:one was the National Authorized Certification Center for the supervision of logistics service platform,the other was the logistics service platform for the supervision of crowdsourcing logistics participation.Later,under the framework of the supervision system,the functions of crowd contract,legal and anonymous identity authentication,intelligent transaction matching,anomaly data analysis and detection,privacy protection and traceability were realized.Then,through the security analysis and transaction supervision component software,the security controllability and operational efficiency of the transaction supervision architecture were verified.Finally,the software component was run on the real crowdsourcing logistics enterprise platform for the actual measurement.The measurement results show that the proposed hierarchical and multi-level smart service transaction supervision framework is safe and controllable.The framework can protect the privacy of users and data,prevent forgery and deception,and realize the auditability and traceability of behaviors and data of users.